Impact of genotype, nutrients and type of cuttings on rose (Rosa spp.)rootstock propagation - Priya, M; Smitha, G R; Sujatha Nair, A; Tejaswini, P; Kalaivanan, D (Journal of Horticultural Sciences, 2025)
An experiment was undertaken to standardize the type of rootstock, nutrient scheduling and type of cuttings for rooting of rose rootstock in factorial completely randomised design with five replications during 2022 to 2023. The treatment includes two rootstocks (V1 : Rosa multiflora and V2 : Natal Briar), four different nutrient doses (N1 : 400:200:200 kg, N2 : 600:200:700 kg, N3 : 450:150:525 kg and N4 : 300:100:350 kg NPK ha-1 year-1) and three types of cuttings (hardwood, semi-hardwood and soft wood). Results revealed that the maximum number of sprouts (1.84), leaves (9.66) and roots (7.83) per cutting, and length of longest root (5.19 cm) were recorded in rootstock Rosa multiflora compared to Natal Briar. Application of 400:200:200 kg NPK ha-1 year-1, recorded maximum survival of cuttings (79.11%), minimum days to first sprouting (8.47) maximum number of sprouts (1.91), leaves (10.54) and roots (9.65) per cutting, and length of longest root (6.33 cm) compared to other fertilizer treatments. Among the different types of cuttings, hardwood cuttings recorded minimum days to first sprouting (8.54), greatest thickness of cutting (7.62 mm), number of roots per cutting (7.67) and length of longest root (5.85 cm). These findings could be used to produce high-quality planting material in rose.